Improved Strategy for Multifractal Characterization of CO2 Adsorption in Micropores - Liu, Gaofeng; Fang, Zhenkun; Zhang, Zhen; Liu, Huan; Lv, Runsheng; Wang, Xiaoming; Chang, Ping; Lin, Jia; Barakos, George (American Chemical Society, 2024)
Currently, two multifractal characterization methods on the complexity and heterogeneity of micropores by the low-temperature CO2 adsorption measurement exhibit systematic differences due to the different studied objects that include the relation curves of the CO2 adsorption capacity vs relative pressure and micropore volume vs micropore size distribution. This situation directly affects the accuracy and applicability of multifractal characterization of micropores. In this article, the four high-rank coal samples are selected to conduct the low-temperature CO2 adsorption experiment. The multifractal parameters are derived and compared to examine the accuracy and applicability of the two multifractal characterization methods of the CO2 adsorption capacity vs relative pressure and micropore volume vs micropore size distribution. The results show that the curves of the partition function, mass scaling function, and singular fractal display the classical multifractal existence characteristic by the methods of the CO2 adsorption capacity vs relative pressure and micropore volume vs micropore size distribution. The generalized fractal dimension parameters of the CO2 adsorption capacity vs relative pressure and micropore volume vs micropore size distribution display a similar variation trend but with different values, by which it is insufficient to determine the relative merits of the two methods. The multifractal singularity parameters (RdR and RdS, ΔfR(αR) and ΔfS(αS)) reflect the impact of the differences in quantity within regions of the same dimension, which present an opposite trend. The multifractal characterization method of micropore volume vs micropore size distribution exhibits greater consistency with the micropore structure in reality, supporting the evidence that the micropore volume vs micropore size distribution method can provide a more accurate and applicative multifractal characterization of CO2 adsorption in micropores than the CO2 adsorption capacity vs relative pressure method. This paper proposes a targeted strategy for improving the accuracy of multifractal characterization of CO2 adsorption in micropores, which provides a scientific basis for the multifractal design strategy of nanoporous materials.